Selected Papers from the 2018 Conference on Community Education and Development: Perspectives on English-Speaking Blacks and Minorities - Black Community Resource Centre (BCRC) (2018)
The Black Community Resource Centre (BCRC) is a growing, resource-based organization that strengthens community capacity by providing professional support to organizations and individuals in need. The Centre is committed to helping visible minority youth rekindle their dreams, and achieve their full potential.We take a comprehensive approach to meet the needs of English-speaking youth. By referring to the “Holistic Project” approach through our community service, we recognize that youth have many needs (e.g., socio-cultural, educational, and economic, etc.) that must be addressed in order for youth to achieve their greatest potential in our society.
event-date: December 6, 2018/December 7, 2018
Keywords: Official Language Minority Community (OLMC)

Black in Quebec : Part 1 - Black Community Resource Centre (BCRC) (2016)

The Education to Employability Study - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
In Québec, both the Black community and the English-speaking community occupy relatively precarious economic and employment positions: both experience higher-thanaverage unemployment rates and earn lower median after-tax incomes compared to the province’s total population. The English-speaking Black Community (ESBC) sits at the intersection of these two communities, and experiences the double marginalization of being both a racial and linguistic minority in Québec.

L'étude éducation à l'emplois (E2E) - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
Au Québec, la communauté noire et la communauté d'expression anglaise occupent toutes deux des positions relativement précaires sur le plan économique et de l'emploi : toutes deux connaissent des taux de chômage supérieurs à la moyenne et gagnent des revenus médians après impôt inférieurs à ceux de la population totale de la province. La communauté noire d'expression anglaise (CNEA) se trouve à l'intersection de ces deux communautés et subit la double marginalisation d'être à la fois une minorité raciale et linguistique au Québec.